ISOLASI SENYAWA KIMIA FRAKSI n-HEKSANA DAUN BILARAN TAPAH (Argyreia nervosa (Burm. F.) ASAL KALIMANTAN SELATAN - Sutomo Sutomo; Putri Helena Junjung Buih; Arnida Arnida (Faculty of Pharmacy, Universitas Muslim Indonesia, 2020)
ABSTRACTOne of the plants that is used empirically by people in South Kalimantan as a traditional medicine is bilaran tapah (Argyreia nervosa (Burm. F.). This plants that has purposed antiinflamation, antimicroba, antidiabetic, diuretic, and aphrodisiac. This research aims to isolate and explore the chemical compounds of n-hexana fraction of A. nervosa leaves. Extraction is conducted by using maceration method. Isolation is conducted by using Vacumn Liquid Chromatography and gravity chromatography column. Identification qualitative assay of compound used TLC test, UV-Vis and FTIR spectrophotometry. The extraction of 500 grams A. nervosa leaves rough powder with 96% ethanol extracts produces 16,92% of rendement. The fractionation of 30 grams ethanol extracts with n-hexane produces 23,60% of rendement. N-hexane fraction by using VLC with n-hexane : ethyl acetate eluent 25:1; 20:1; 15:1; 10:1; 9:1; 8:2; 7:3 ; 6:4) v/v and methanol : etyl acetate (1:4) v/v produces fractions A, B, C, D, E, F, G, H, and I. Fraction F was chosen for isolation using PTLC with n-hexane :etyl acetate eluent (8:2) v/v. Fraction C is chosen to be isolated by using gravity chromatography column with n-hexane : ethyl acetate eluent (25:1) v/v. TLC qualitative test with H2SO4 10% and Liebermann-Burchard reagent shows that C-4 isolates contains terpenoid compounds. Analysis of C-4 isolates by using UV-Vis spectrophotometry reach peak at λ 245 nm. Analysis FTIR spectra shows that the functional groups of C-4 isolates are -OH (3309.85 cm-1), -CH aliphatic (2939.52 cm -1 and 2870.08 cm-1), C = C (1635.64 cm- 1) and C-O (1033,85 cm-1).